Influence of in-situ Soil and Water Conservation Measures on Performance of Nagpur Mandarin - Panigrahi, P; Srivastava, A K; Huchche, A D (Journal of Agricultural Engineering, 2009)
The loss of abundant runoff and soil during the rainy season (June-September) followed by sub-optimal available soil moisture at root zone of the plants during critical growth stages during post-monsoon is one of the major causes of low productivity and declining of Nagpur mandarin orchards in central India. A study was conducted during 2003-2007 to evaluate the effects of different in situ soil and water conservation treatments on one year old Nagpur mandarin (Citrus reticulata blanco). All conservation treatments (continuous bunding, continuous trenching, and staggered trenching between rows) were effective in reducing loss of runoff, soil and nutrients, and imparted a favourable response on vegetative growth, fruit yield and quality as compared to the control. Continuous trenching gave the best response conserving 28.4% runoff, 24.9% soil loss, 42.6% N, 45.8% P, and 47.6% K over control, besides 29.2% higher fruit yield (9.60 kg/plant). Among different fruit quality parameters (TSS, juice percentage and acidity), juice percentage and TSS were significantly higher in continuous trenching over control.